Copper-Mediated Direct Aromatic ortho-C–H Cyanation by AIBN - Zhou, Aijun; Wang, Zhenlian; Chen, Fan; Qian, Peng-Cheng; Cheng, Jiang (Synlett, 2022)
We have developed a copper-mediated chelation-assisted direct aromatic ortho-C–H cyanation that uses AIBN as a safe cyanation reagent. The substrate scope included indoles, pyrroles, a carbazole, and a thiophene.
Keywords: copper catalysis; cyanation; C–H bond activation; AIBN; radical reaction; safety